2011
DOI: 10.1164/rccm.201002-0181oc
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Death Is an Important Contributor to Oxidant-mediated Acute Lung Injury

Abstract: Rationale: Acute lung injury and the acute respiratory distress syndrome are characterized by increased lung oxidant stress and apoptotic cell death. The contribution of epithelial cell apoptosis to the development of lung injury is unknown. Objectives: To determine whether oxidant-mediated activation of the intrinsic or extrinsic apoptotic pathway contributes to the development of acute lung injury. Methods: Exposure of tissue-specific or global knockout mice or cells lacking critical components of the apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 64 publications
0
78
0
Order By: Relevance
“…Previous studies from our laboratory and others have demonstrated that these cell death mediators are critical regulators of HALI (30,50,56). To understand the mechanism of increased HALI in NOS2 null mutant young adult mice, we documented increased expression of Ang2, a molecule previously shown by us to be a critical regulator of cell death in HALI (23).…”
Section: Nos2mentioning
confidence: 74%
See 1 more Smart Citation
“…Previous studies from our laboratory and others have demonstrated that these cell death mediators are critical regulators of HALI (30,50,56). To understand the mechanism of increased HALI in NOS2 null mutant young adult mice, we documented increased expression of Ang2, a molecule previously shown by us to be a critical regulator of cell death in HALI (23).…”
Section: Nos2mentioning
confidence: 74%
“…The involvement of key cell death regulators in the process of HALI has been reported by us (23,27,28,49) and others (50). Aside from the membrane (extrinsic) pathway that triggers cell surface "death receptors," such as Fas, which binds Fas-L and activates caspase 8 (51,52), many other stimuli use mitochondrial dysfunction to signal the cell death response.…”
Section: Nos2mentioning
confidence: 83%
“…Hyperoxia results in increased pulmonary expression of NF-kB-regulated proapoptotic proteins (BAX [46]), proinflammatory cytokines (IL-1b, CXCL1 [3,47]), and pro-oxidant enzymes (COX-2 [48]). We found hyperoxia-induced induction of BAX, IL-1b, CXCL1, and COX-2 in both WT and AKBI mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mclk1 +/− mice lack one copy of an enzyme that is necessary for the synthesis of the antioxidant and redox co-factor ubiquinone [47]. This leads to numerous metabolic changes but in particular to an increase in mitochondrial oxidative stress [48], which is deleterious under some experimental conditions [49]. Surprisingly these mutant mice not only live longer than wild-type siblings [50], they also show a much slower development of biomarkers of aging, including a slower loss of mitochondrial function [51].…”
Section: Ros Signaling Affects Aging and Lifespanmentioning
confidence: 99%